Pemanfaatan Perpustakaan Sebagai Sumber Belajar di Panti Asuhan Wira Lisna Mata Air Padang - Putra, Riko Sapta; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This study aimed to describe: (1) use of the library as a learning resource, (2) the constraints faced in the use of the library as a learning resource, and (3) what is being done Wira Lisna orphanage library in providing learning resources. Data were collected through observation and interviews in the Library Orphanage Lisna Wira. Data analysis was performed deskriptif.Dari result of the discussion was found as follows: First, the use of students in the library at the orphanage Padang Springs Wira Lisna not fully utilized. This is because the librarians are less oriented in building students' interest in reading, in terms of a collection of books owned by the poor students complete. Collection consisted only of old books, there is no renewal of the collection of its kind. This is a cause that underutilized library as a learning resource., As a protÃ©gÃ© of elementary, middle and high school lesson rather seek to internet sites that tend to bring the ill effects on the students. Second, constraints are: (1) the library is not professionally managed, so that visitors do not know the importance of the library as a learning resource for children, (2) the lack of reading materials in the library collection Panti AsuhanWira Lisna so visitors do not use the library because libraries are not material can meet the needs of visitors, (3) the efforts made in the use of the library are: (1) the holding of the renewal of the collections in the Library Orphanage Lisna Wira, (2) open and direct students learning Librarianship as a guideline, (3) improve facilities and infrastructure, and (4) expand and improve human resources in the Library Orphanage Lisna Wira. Keyword: learning resources; use the library